2014
DOI: 10.1002/int.21692
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Monotonic Averaging Functions

Abstract: Monotonicity with respect to all arguments is fundamental to the definition of aggregation functions. It is also a limiting property that results in many important nonmonotonic averaging functions being excluded from the theoretical framework. This work proposes a definition for weakly monotonic averaging functions, studies some properties of this class of functions, and proves that several families of important nonmonotonic means are actually weakly monotonic averaging functions. Specifically, we provide suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…Recently, several generalizations of aggregation functions have been introduced, considering some weaker forms of monotonicity, in particular, weakly monotone aggregation functions and preaggregation functions . Then one can consider set‐based weakly increasing aggregation functions (ie, such set‐based functions which, for each arity n, form an n‐ary weakly increasing aggregation function), or set‐based preaggregation functions, compare Example .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several generalizations of aggregation functions have been introduced, considering some weaker forms of monotonicity, in particular, weakly monotone aggregation functions and preaggregation functions . Then one can consider set‐based weakly increasing aggregation functions (ie, such set‐based functions which, for each arity n, form an n‐ary weakly increasing aggregation function), or set‐based preaggregation functions, compare Example .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, for example, Ff(0.2,0.3)=0.06<Ff(0.4,0.4)=0.4>Ff(0.5,0.6)=0.3. Observe that Ff(0,,0)goodbreakinfix=0 and Ff(1,,1)goodbreakinfix=1, that is, Ff fulfils the boundary conditions of aggregation functions. More, for each boldxgoodbreakinfix∈[0,1]n and each boldcgoodbreakinfix=(c,,c)goodbreakinfix∈[0,1]ngoodbreakinfix,0.33emngoodbreakinfix∈double-struckN, we have Ff(boldx+boldc)goodbreakinfix≥F(x), that is, Ff is weakly increasing, and it can be concluded that Ff is a proper preaggregation function …”
Section: Set‐based Extended Functionsmentioning
confidence: 99%
“…One may note that the averaging function EGBM is not monotone with respect to the parameters p and q . However, it is monotone in weaker sense . That is illustrated in the following theorem: Theorem For a fix x[0,1]n, the averaging function EGBMp,q is weakly monotone with respect to the parameters p and q , that is italicEGBMp+a,q+afalse(xfalse)italicEGBMp,qfalse(xfalse)foranyaR.…”
Section: Extended Geometric Bonferroni Meanmentioning
confidence: 99%
“…This is the case, for instance, of some subsethood measures (see [22]); • Many functions used for comparison of data are also directionally increasing. In particular, this is the case of those based on component-wise comparison by means of the Euclidean distance |x − y|, as for restricted equivalence functions [23]; • Weakly increasing functions ( [8]) are a particular case of directionally increasing functions, with r = (1, . .…”
Section: Directional Monotonicitymentioning
confidence: 99%